Sommer 2024: Weiterhin kein konjunktureller Aufschwung in Sicht - Torsten Schmidt; Niklas Benner; Boris Blagov; Maximilian Dirks; Daniela Grozea-Helmenstein; Niklas Isaak; Robin Jessen; Florian Kirsch; Stefan Kotz; Clara Krause; Philip Schacht-Picozzi; Klaus Weyerstraß (RWI Konjunkturberichte, 2024)
Die deutsche Wirtschaft stagniert seit Ende des Jahres 2022. Die Erwartung, dass mit dem Auslaufen des Energiepreisschocks aus jenem Sommer eine Erholung einsetzt, hat sich bisher nicht erfüllt. Dabei haben sich einige Rahmenbedingungen inzwischen spürbar verbessert. Die Inflation hat deutlich nachgelassen, die real verfügbaren Einkommen steigen inzwischen kräftig und die EZB hat die Zinsen ein erstes Mal gesenkt und weitere Senkungen in Aussicht gestellt. Dennoch hat die gesamtwirtschaftliche Nachfrage bisher keinen Schwung entfaltet. Nach der Ausweitung der Produktion im ersten Quartal ergab sich ein erneuter Rücksetzer. Dazu trug bei, dass die Exporte wenig Dynamik aufweisen. Das Expansionstempo bleibt derzeit hinter dem des Welthandels zurück. Die deutschen Unternehmen verlieren dadurch Weltmarktanteile. Dies dürfte auch ein Grund dafür sein, dass sich die deutschen Unternehmen mit Investitionen zurückhalten. Allerdings lässt sich der kräftige Rückgang der Investitionsnachfrage im zweiten Quartal nicht allein damit erklären. Vielmehr dürften binnenwirtschaftliche Faktoren ebenfalls eine erhebliche Rolle spielen. Dazu zählen die Nachwirkungen des starken Anstiegs der Unsicherheit zu Beginn dieses Jahres. Die Unternehmen warten nach wie vor auf zielführende Weichenstellungen, die geeignet sind, die angestrebten Transformationsziele, insbesondere beim Energiesystem, mit dem Ziel der Bereitstellung eines attraktiven Wirtschaftsstandorts zu versöhnen. Da diese Belastungen fortbestehen dürfte das BIP auch in der zweiten Jahreshälfte weitgehend stagnieren. Erst ab dem kommenden Jahr ist damit zu rechnen, dass die Exporte wieder etwas an Schwung gewinnen. Dies dürfte dann auch die Ausrüstungsinvestitionen etwas beleben. Die Belebung der Binnenwirtschaft wird wesentlich von der privaten Konsumnachfrage bestimmt. Die weiterhin steigenden Realeinkommen dürften nach und nach zu einer steigenden Konsumnachfrage führen. Für den Jahresdurchschnitt 2024 ist zu erwarten, dass das BIP um 0,1% ausgeweitet wird. Im Jahr 2025 wird das BIP wohl um 0,9% und im Jahr 2026 um 1,4% steigen. – – The German economy has been stagnating since the end of 2022. Expecta- tions that the end of the energy price shock would trigger a recovery have not yet materialised. Some general conditions have improved noticeably in the meantime. Inflation has eased significantly, real disposable income is now rising sharply, and the ECB has cut interest rates for the first time and held out the prospect of further reductions. Nevertheless, overall economic demand has not yet gained any momentum. The expansion in production in the first quarter was followed by another setback. The fact that exports are showing little momentum contributed to this. The pace of expansion is currently lagging behind that of global trade. As a result, German companies are losing global market shares. This is probably also a reason why German companies are holding back on investments. However, this alone cannot explain the sharp decline in investment in the second quarter. Domestic economic factors are also likely to play a role here. One reason is probably also the after-effects of the sharp rise in uncertainty at the beginning of this year. Companies are still waiting for effective decisions which are suited to align transformative objectives, especially those regarding the energy system, with the provision of an attractive business location. This also seems to be a key reason why private consumption fell in the second quarter, even though real disposable incomes rose sharply. As these burdens persist, GDP is likely to remain largely stagnant in the second half of the year. Exports are not expected to regain momentum until next year. Their increase would also tend to revitalise demand for equipment investments somewhat. The revitalisation of the domestic economy will be largely driven by private consumer demand. The continued rise in real incomes is likely to lead to a gradually increase of consumer demand. GDP is expected to expand by 0.1% on average in 2024. GDP will probably increase by 0.9% in 2025 and by 1.4% in 2026. Despite the weak economy, the labour market is proving to be quite robust. Although unemployment continued to rise quite sharply in the first half of the year, employment also increased at the same time. Despite falling unemployment, employment is likely to reach its peak in the course of the coming year, as the number of people entering the labour market is falling for demographic reasons. On an annual average, employment is likely to stagnate in 2025 and fall by around 80 thousand people in 2026. The unemployment rate is expected to fall from 6.0% (2024) to 5.9% (2025) and 5.7% (2026), respectively. Inflation has fallen more sharply than expected since the forecast in June and is expected to be 1.9% in August. Our forecast for the inflation rate for 2025 and 2026 is 2% for each year. The general government budget deficit is likely to fall to roughly 89 billion euro in the current year. Government revenue is rising sharply. On the expenditure side, the decline in subsidies due to the abolition of the 'price brakes' will have the greatest impact. The budget deficit is expected to fall to 68 billion euro in 2025 and to 62 billion euro in 2026.
Keywords: 330